LEGAL CERTAINTY OF ELECTRONIC LAND CERTIFICATES IN LAND REGISTRATION IN INDONESIA - Lestari Sutrisno, Windi; Nur Widyanti, Amelia; Akkapin, Supaphorn (Penerbit Lafadz Jaya, 2025)
This research aims to analyze the legal certainty of electronic land certificates in land registration in Indonesia, with a normative approach through literature studies that analyze various related laws and regulations. Electronic land certificates are expected to provide convenience and transparency in the land registration process. However, the implementation of this system faces challenges, especially related to the validity of electronic documents, the misuse of multiple certificates, and the role of notaries in the installation of mortgage rights. This study found that despite efforts to strengthen legal certainty through regulations related to electronic land registration, implementation and law enforcement issues still need to be improved. Therefore, it is necessary to strengthen regulations, increase public understanding, and stricter supervision of the implementation of electronic land registration in Indonesia.